Can visceral leishmaniasis be eliminated from Asia? - A. Joshi; J.P. Narain; C. Prasittisuk; R. Bhatia; Ghalib Hashim; Alvar Jorge; M. Banjara; A. Kroeger (Journal of Vector Borne Diseases, 2008)
Data on the burden of visceral leishmaniasis (VL) in Indian sub-continent are vital for elimination programme planners for estimating resource requirements, effective implementation and monitoring of elimination programme. In Indian sub-continent, about 200 million population is at risk of VL. Nearly 25,000–40,000 cases and 200–300 deaths are reported every year, but these are grossly underestimates. Recent well-designed multicentric studies identified VL burden of 21 cases/10,000 among sampled population in Indian sub-continent (Bangladesh, India and Nepal). This estimates 4,20,000 cases per 200 million risk population clearly indicating that the disease is highly under-reported. Chemical and environmental vector control studies show that the indoor residual spraying (IRS) and long-lasting insecticidal nets (LLINs) are effective and significantly reduce sandfly densities. The findings documented from different sources revealed that some gaps and weakness in existing policies for introducing VL vector control interventions. Our studies emphasize the need of integrated vector management with both IRS and LLIN vector control interventions. Active case detection with rK39 strip test as diagnostic tool is the key element for detection of VL cases. The use of oral drug miltefosine for the treatment after assessing feasibility at community level is important. Kala-azar elimination in Indian sub-continent is possible if elimination programmes ensure access to health care and prevention of kala-azar for people at risk with particular attention to the poorest and marginalized groups. The evidence-based policy should be designed that motivates to implement the programmes, which will be cost-effective. Maintaining the acceptable level of incidence requires public awareness, vector control, appropriate diagnosis and treatment. The five pillars of VL elimination strategies identified are: early diagnosis and complete treatment; integrated vector management and vector surveillance; effective disease surveillance through passive and active case detection; social mobilization and building partnerships; and clinical and operational research which need to be re-enforced to effective implementation.